Insights / Student's Book - Farthing Matthew; Pulverness Alan (Macmillan Publishers And English Language Arts, 1989)
A complete course for students at a pre-FCE Level. Who are You?, Safety First, Read All About It, New Departures, Technology or Tradition, Wheels, Imagine, Travelers' Tales, A Changing World, Rubbish and Radio, The Ground Beneath Us, The World Around Us, Mysteries, Man and Nature, Runaway.